Modeling Tree-Induced Ground Subsidence in Compacted Clay: An Investigation into the Effects of Contrasting Tree Species - Yuliana; Apriyono, Arwan; Kamchoom, Viroon; Leung, Anthony Kwan; Laokhongthavorn, Laemthong (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 28, 2023)
The subsidence of structures founded on clay soils has been an increasingly prevalent issue in recent years, primarily due to the cyclic contraction and expansion of soil in response to root-water uptake by neighbouring trees and the seasonal variations. Traditional models for simulating the complex interplay between soil, vegetation, structure, and climate often entail intricate root-water uptake models that require extensive empirical data. This study employed a simplified modelling approach to assess the impact of tree root-water uptake on seasonal changes in pore water pressure and ground movement in unsaturated soils. By defining a root zone and incorporating multiple internal head boundaries in PLAXIS 2D, the hydromechanical behaviour of the unsaturated soil can be effectively modelled. The results of this model, which consider the soil moisture changes induced by mature deciduous Silver Birch and evergreen Leyland Cypress trees, were validated against reported case studies. Our findings suggest that significant differential settlements (ranging from 1/100 to 1/10, depending on water uptake, soil plasticity, and season) may occur near the edge of the root zone as a result of tree root-water uptake.